Polycationic Pillar[5]arene Derivatives: Interaction with DNA and Biological Applications. Issue 51 (11th November 2013) - Nierengarten, Iwona; Nothisen, Marc; Sigwalt, David; Biellmann, Thomas; Holler, Michel; Remy, Jean‐Serge; Nierengarten, Jean‐François
Abstract Dendritic pillar[5]arene derivatives have been efficiently prepared by grafting dendrons with peripheral Boc‐protected amine subunits onto a preconstructed pillar[5]arene scaffold. Upon cleavage of the Boc‐protected groups, water‐soluble pillar[5]arene derivatives with 20 (13) and 40 (14) peripheral ammonium groups have been obtained. The capability of these compounds to form stable nanoparticles with plasmid DNA has been demonstrated by gel electrophoresis, transmission electron microscopy (TEM), and dynamic light scattering (DLS) investigations. Transfection efficiencies of the self‐assembled 13/pCMV‐Luc and 14/pCMV‐Luc polyplexes have been evaluated in vitro with HeLa cells. The transfection efficiencies found for both compounds are good, and pillar[5]arenes 13 and 14 show very low toxicity if any.